PEMIKIRAN DAN KRITIK IRENE SCHNEIDER TENTANG AUTENTISITAS HADIS - Farid Adnir; Syukri Syukri (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
The study of Hadith developed in line with the development of science and Islam, so the study of this hadith began to be of interest to Muslim scholars, no less important is that western scientists also began to be interested in studying this hadith, although the basis and purpose of their research was different from that of Muslims, there were those who said that due to the renaissance, namely doubting all knowledge, so they began to re-examine all knowledge, including this effect on Islamic studies and thought, it is said that western scholars study this hadith driven by historical interests, so when they research hadith they are more likely to say only as a model of thought and not as legal texts. Western thinkers in studying this Hadith are based on nothing but wonder and curiosity, to what extent can these Islamic texts be trusted to be true, so that they have such a large mass appeal and followers, are getting more and more stretched and Islamic motivations are increasing. Western scholars feel the need to research and examine the sacred texts according to Muslims. So that western scholars have several approaches in studying hadith that have developed to date. Irene Schneider is an orientalist who is very interested in Islamic studies, she is very diligent in studying Islamic studies, culture, the history of Islamic thought, Irene does a lot of research related to Islamic law and the history of Islamic law, she also conducts research related to gender studies, relationships countries with people in the contemporary Islamic world, including how Muslims stretch in Germany. Irene Schneider's thoughts we can say that theoretically and scientifically it can be said that Irene was greatly influenced by Josep Schacht, we can see that several theories and concepts introduced by Josep Schachat were widely developed by Irene and he published in subsequent research and theories, especially rather he is able to say he is skeptical of the hadith of the Prophet SAW. and Islamic traditions, although on certain issues Irene also has differences with Josep Schacht, such as the Hadith that are based on the tabi'in.